Investigation of Macrophyte for Bioproduct Potential: A Review - MOHAMAD A'ASHRI, SITI NUR EZIANIE; Radin Mohamed, Radin Maya Saphira (Recent Trends in Civil Engineering and Built Environment, 2021)
Overpopulation of macrophyte in drainage ditch can lead to a problem in maintenance and reduce the efficiency of the system. Therefore, this study aims to review the feasibility of Eleocharis dulcis (E. dulcis) for bioproduct potential as a sustainable use of macrophyte. A sustainable approach in the production of the product is crucial to overcome the risks and impacts to the environment. The selection of macrophyte as new material to produce straw bioproduct can be the solution to the problems surrounding conventional plastic straws. Meanwhile, bio-based fuels production can lead to solve the needs of renewable sources of fuels for energy generation applications. In conclusion, E. dulcis had the potential for bioproduct and the benefits of macrophyte as bioproducts is impactable not only for the drainage ditch problem but also for other environmental problems.